WhatsApp and English Learning: Students’ Perceptions and Challenges in Pandemic Era - Juliana, Rena (UPT. Pengembangan Bahasa IAIN Zawiyah Cot Kala Langsa, 2021)
Since the pandemic era due to Covid-19, WhatsApp has become an application that is widely used for online learning. In the new normal era, WhatsApp was still the application most widely used by lecturers and students because sending teaching materials was easy and fast. This study investigated students’ perceptions and challenges of utilizing WhatsApp in English language learning amid the pandemic era. The method used was a qualitative method. The researcher used a purposive sampling technique in selecting the participants. The participants in this study amounted to 12 EFL students of 2nd semester of STAIN Teungku Dirundeng Meulaboh. A semi-structured interview was used as data collection techniques. The interview data were analyzed using the Miles and Huberman flow model. The results showed that students used social media to learn and improve their English skills. WhatsApp is the most used application, considered fun, comfortable, helpful, and easy to use. WhatsApp is not only effective and time-saving, it also motivates students in learning English. In addition, WhatsApp uses less internet quota than other online applications. Even so, the internet connection, internet quota, and storage capacity on their devices are still challenges for the students. It can be concluded that the students have positive perceptions of using WhatsApp to learn English.